Chromium adsorption using Sargassum filipendula algae waste from alginate extraction: Batch and fixed-bed column studies - Talles Barcelos da Costa; Thiago Lopes da Silva; Camila Stéfanne Dias Costa; Meuris Gurgel Carlos da Silva; Melissa Gurgel Adeodato Vieira (Chemical Engineering Journal Advances, 2022)
Chromium is a toxic metal widely used in several industrial activities, being frequently found in industrial effluents. The presence of chromium in its soluble ionic form Cr(III) is related to health risks, damage to living beings and to the environment. In this work, the capture of Cr(III) using alginate extraction residue (RES) from the Sargassum filipendula algae was evaluated to investigate the adsorption properties of this waste material. The study steps included batch and continuous adsorption assays, characterizations, and desorption evaluation. The adsorbent residue was not submitted to pre-treatment steps. The investigation of chromium adsorption and the fluid dynamic study are presented in this work. The equilibrium and thermodynamic studies indicated that the uptake of Cr(III) by the RES occurred spontaneously, endothermic, and energetically favorable on a heterogeneous surface with energetically distinct sites, mainly by chemisorption. The Freundlich and Dubinin-Radushkevich, and pseudo-second order models showed better fit to the equilibrium and kinetic experimental data, respectively. In the continuous fixed-bed system, the breakthrough curves showed a smaller mass transfer zone under flow rate and Cr(III) inlet concentration conditions of 0.5 mL/min and 1.0 mmol/L, respectively. The low desorption percentages corroborate the chemical nature of the bonds involved in adsorption. The best result of 67.5% was obtained with the combined eluent of HCl and CaCl2, both at 1 mol/L. SEM and EDX analyzes showed that ion exchange is involved in the adsorptive process with a reduction in the amount of light ions (Na, Ca, Mg, and K) on the RES surface. The characterization analyzes indicated that hydroxyls are the main group involved in the adsorption of metal that occurred on the surface of the RES.